Grammatical Errors Committed by the Student-Teachers in Their Theses - Monalisa Monalisa; Syahrial Syahrial; Urip Sulistyo; Mukhlash Abrar (Indonesian Language Education and Applied Linguistics Reviews, 2025)
This study aimed to recognize to what extent grammatical errors occurred in undergraduate theses. A qualitative content analysis was employed on 25 theses reported by student-teachers. The writer hired the four steps of errors analysis proposed by Ellis (1997). To adjust to the study's purpose, the two significant taxonomies of errors - the linguistic category and surface taxonomy strategy – were used to make the errors easily classified and explained. Interviews were also conducted to student-teachers and their theses advisors. The deep interaction between the writer and the theses was done by reading them intensively to ensure truthful data. It was found 1397 erroneous sentences that were spread out into simple, compound, complex, and faulty sentences, and they derived 2278 grammatical errors. In relation to the ways of language learners make errors, they were broken into five pieces of the process: omission, misinformation, addition, misordering, and selection. The next findings were source of error issues which consisted of interlingual errors (transfer of structure) and intralingual ones (overgeneralization, incomplete application of rules, false analogy, misanalysis, exploiting redundancy). The results of discussion on the findings led to reflect the student-teachers language status, mainly their writing skill in the position of developmental stage. For accuracy, there are three ways to respond these errors: error corrections, strategy training, and grammar instruction in the context of academic writing. A proto syllabus of Thesis Writing course is proposed to facilitate students in producing adequate thesis.